INNOVATION OF SINBIOTIC FORMULA FOR THE GROWTH OF WHITE SHRIMP LARVAE (Litopenaeus vannamei) - Sumardi, Sumardi; Nugroho Ekowati, Christina; Linirin Widiastuti, Endang; Rohmawati Bareta, Ainun; Sarno, Sarno (BIOVALENTIA: Biological Research Journal, 2021)
In the hatchery of white shrimp larvae, there are some problems, such as a decreased water quality and diseases caused by bacteria which cause a decrease in shrimp growth. The solution to reduce these problems is by applying synbiotics. This research aimed to make an innovative synbiotic formula for the absolute length growth and survival rate of white shrimp larvae (Litopenaeus vannamei) as well as the total number of bacteria and the number of Vibrio sp. In this study, there were four treatments, as follows: C-: negative control (without synbiotic application) C+: positive control (commercial synbiotic) P: probiotic 2.5 x 105 cfu/ml and prebiotic 1,5 ppm Q: probiotic 5 x 105 cfu/ml and prebiotic 1 ppm R: probiotic 7,5 x 105 cfu/ml and prebiotic 0,5 ppm S: probiotic 106 cfu/ml and prebiotic 2 ppm, each treatment with four repetitions. This research was set up in a completely randomized design experiment using twenty-four plastic tanks with 50 L total volume filled with 20 L sterile sea water and stocked with 4,000 nauplii in the PT. Citra Larva Cemerlang hatchery, Kalianda, Lampung. Variables observed in this research were survival rate, absolute length growth, total bacterial and Vibrio sp. counts, and water quality in the white shrimp larvae (Litopenaeus vannamei). The results showed that the best survival rate is in treatment S (probiotic 106 cfu/ml and prebiotic 2 ppm) (87.7%), the highest absolute length growth is in treatment P (3.8 mm), the highest total bacteria was in treatment S (11.1 log cfu/ml), and the best total Vibrio sp. is in treatment S (3.5 log cfu/ml). Water quality of the six treatments shows results that are still in normal conditions following Indonesian National Standard SNI 7311: 2009.